La R&D de défense en France : quels changements depuis la guerre froide ? - Sylvain Moura (Revue de la Régulation)
The article examines the evolution of the French military research and development system in a post-Cold War context using an institutionalist approach based on public policy analysis and Jullien and Smith’s model. While adaptations to the new geopolitical and economic context have been made, the defence policy has kept the country in the arms race. In doing so, the relationship between the state and the defence companies remains very close, much like during the Cold War.